Journey to Success: Exploring How Cultural Changes Affect the Academic Performance of Indonesian Final-Year Students - Niko Syahputra; Aini Syahira Jamaluddin (IJECA (International Journal of Education and Curriculum Application), 2024)
The research being undertaken at an international university, seeks to examine how changes in culture affect the academic performance of Indonesian final-year students. The research includes qualitative approaches, including in-depth interviews with six respondents who are students in areas such as Media and Communication, Elementary Education, and Business Administration. The study investigates the difficulties encountered by these students including language hurdles, regional differences, and problems adjusting, all of which affect how well students do in school, the impact of cultural changes on their academic performance, and the coping techniques used. Key results include the importance of cultural diversity at universities, barriers to academic achievement, and support systems and events that help Indonesian students adjust to a multicultural environment. The research highlights the need for strong support mechanisms for overseas students' academic journeys and achievement, especially those enduring cultural adjustments.